In the Threshold: Writing Between-the-Two - Mazzei, Lisa A.; Jackson, Alecia Y. (International review of qualitative research, 2013)
In this paper, we describe our encounters in and passes through the figuration of the threshold as producing writing between-the-two: or, loss of the individual subject. We describe how in the threshold, we meet in that in-between space, a space of shared deterritorialization in which we constitute one another. Also, we describe writing between-the-two in the threshold as a site of embodiment, of affect. In thinking of how to articulate our way of thinking and writing together as between-the-two and as different than a collaborative project where two “I”s contribute pieces both with and independent of the other, we take our cue from Ken Gale and Jonathan Wyatt's (2009)Between the Two. In this book, they articulate a way of thinking and writing inspired by Deleuze and Guattari's collaborative work as that which is not a working together, but a working in the gap “between the two” (Deleuze & Parnet, 1987/2002, p. 13). This spark of creativity in the gap is both like and unlike what we will explain in this article. Like Gale and Wyatt, we lean on figurations and concepts in the writings of Deleuze and Guattari as a referent; however, our between-the-two is pursued more deliberately through a materialist knowing in being that produces our becoming with and in a digital threshold.